2019
DOI: 10.5590/josc.2019.11.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Practice Nursing in Nigerian Healthcare: Prospects and Challenges

Abstract: This study explored the prospects and challenges of introducing advanced practice nursing (APN) in the Nigerian health system. It sought to address the following: career pathways for registered nurses and midwives, advanced duties performed by them and the circumstances, their views and willingness for autonomous practice, and doctors’ degree of acceptance. Research population composed of registered nurses, midwives and medical doctors in primary healthcare. The conceptual framework for this study was based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, a study conducted in South Africa found that implementing a nurse-led trauma service was associated with improved patient outcomes, including reduced mortality rates and shorter hospital stays; however, the enhanced outcomes might be seen as a result of both system-and nursing-related contributions, illustrating the importance of integrating nursing expertise within the trauma care system to improve patient outcomes (Christmals & Armstrong, 2019a, 2019bWearmouth & Smith, 2019). Similarly, a study conducted in Nigeria found that utilizing APNs in emergency care was associated with improved triage and patient outcomes (Chimezie & Ibe, 2019). A study in Uganda also showed that investing in APNs increased access to emergency care and improved the quality of care and cost-effectiveness of care provided (Terry et al, 2012).…”
Section: Sources Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study conducted in South Africa found that implementing a nurse-led trauma service was associated with improved patient outcomes, including reduced mortality rates and shorter hospital stays; however, the enhanced outcomes might be seen as a result of both system-and nursing-related contributions, illustrating the importance of integrating nursing expertise within the trauma care system to improve patient outcomes (Christmals & Armstrong, 2019a, 2019bWearmouth & Smith, 2019). Similarly, a study conducted in Nigeria found that utilizing APNs in emergency care was associated with improved triage and patient outcomes (Chimezie & Ibe, 2019). A study in Uganda also showed that investing in APNs increased access to emergency care and improved the quality of care and cost-effectiveness of care provided (Terry et al, 2012).…”
Section: Sources Of Evidencementioning
confidence: 99%
“…These nurses can order relevant investigations, diagnose, and treat a wide range of conditions and are often involved in the management of critically ill patients, including doing medical procedures that can save patients. In addition, they can provide holistic support and health education to patients and their families, improving patient satisfaction and overall health outcomes (Chimezie & Ibe, 2019). However, despite the potential benefits of APN in emergency care, there are still significant challenges to their implementation and integration into healthcare systems in Africa.…”
mentioning
confidence: 99%